Enhancing biology students' academic achievement in reading comprehension through an innovative strategy in university context: “REVOLUTION” strategy - Khataee, Elnaz; Khataee, Elham; Khataee, Mohammad Javad; Khademi, Hanif (Penerbit Universiti Kebangsaan Malaysia, 2023)
This paper has arisen from diligent studies on the reading comprehension ability of biology students in the university EFL context. The purpose of the paper is to enhance biology students’ academic achievement in reading comprehension through an innovative strategy inspired from the word “REVOLUTION”. The strategy is introduced in the present paper and it is developed and implemented for the first time in reading comprehension instruction. To collect the relevant data, a questionnaire, interviews, reading comprehension texts and tests were used. Participants were 67 EFL learners studying plant biology at two universities in Iran. They were assigned into two groups of experimental and control. In the experimental group, the REVOLUTION strategy was used as a treatment in teaching reading comprehension, while in the control group, the teacher read out the text and asked students to listen, the teacher was supposed to answer the students' important questions. The main findings of the study showed that when the teacher applied the REVOLUTION strategy, the students had a much better performance on the reading comprehension tests. The conclusion to be drawn from this study is that the implementation of this strategy can be useful in improving the reading comprehension of university students, it enhances learners’ academic achievement in reading comprehension and also helps them to understand academic texts easily and effectively.